2018
DOI: 10.1111/pde.13543
|View full text |Cite
|
Sign up to set email alerts
|

Anogenital warts in children: Analysis of a cohort of 34 prepubertal children

Abstract: Anogenital warts are caused by infection with the human papillomavirus. We reviewed the clinical data of 34 children younger than 13 with anogenital warts referred to the department of dermatovenereology of a tertiary care hospital. Suspicion of sexual abuse was raised in 11 (32.4%). Human papilloma virus testing and genotyping was performed in 19 (55.9%) children, and human papilloma virus type 16 was found in 4, which raises the question regarding what type of follow-up is required for children infected with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 5 publications
0
19
0
1
Order By: Relevance
“…The results of studies on AGW in children are partly contradictory. Possibly, this can be explained by differences in study populations, selection bias, different age ranges, limited information on confirmed sexual abuse, low numbers of cases examined, different types of samples (biopsies, swabs) and differences in sensitivity and covered type spectrum of the HPV‐typing assays used 16,17,23–27 . The present study is one of the few studies with a larger number of children (55 children) in a multicentre setting.…”
Section: Discussionmentioning
confidence: 94%
“…The results of studies on AGW in children are partly contradictory. Possibly, this can be explained by differences in study populations, selection bias, different age ranges, limited information on confirmed sexual abuse, low numbers of cases examined, different types of samples (biopsies, swabs) and differences in sensitivity and covered type spectrum of the HPV‐typing assays used 16,17,23–27 . The present study is one of the few studies with a larger number of children (55 children) in a multicentre setting.…”
Section: Discussionmentioning
confidence: 94%
“…Girls are more frequently affected than boys, at a ratio of 3:1.7 [3]. However, little is known about the epidemiology of the virus in the pediatric population In a cohort of 34 prepubertal children, the perianal localization interested 67,6% of cases and was the most frequent site [2]. Typing the HPV virus is useful when making a diagnosis and assessing children with genital warts.…”
Section: Discussionmentioning
confidence: 99%
“…Several HPV types can cause anogenital warts. Their occurrence in childhood should require some consideration and careful examination to mean their transmission [2]. Herein we report a new case of vulvar wart in an 8-year-old child.…”
Section: Introductionmentioning
confidence: 94%
“…In infants, infection may result from mother to infant transmission, through an infected birth canal, autoinoculated after birth from a nongenital area to genitalia, or by sexual abuse. 1 Giant CA, also known as Buschke-Lowenstein tumor, is a rare dis- Management of giant condylomata in infants is still a challenge. In recent guidelines, recommendations and randomized control trial for children are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In infants, infection may result from mother to infant transmission, through an infected birth canal, autoinoculated after birth from a nongenital area to genitalia, or by sexual abuse 1 …”
Section: Introductionmentioning
confidence: 99%